(untitled) (Czech Journal of International Relations, 2010)
Mats Braun: Modernisation Unchallenged: The Czech Discourse on European Unity. 1st ed. Prague: Institute of International Relations, 2008, 152 stran, ISBN 978-80-86506-72-2 (signatura knihovny ÚMV De 55 422 PK).